Diagnosis of central nervous system infection by CSF sampling of the myelomeningocele sac as an alternative to ventricular tap - Kaplan, Metin; Ucler, N.; Bayrakli, F.; Duz, B.; Erol, F.S. (Neurocirugia, 2010)
Background. Infection significantly affects mortality and morbidity in myelomeningocele cases. Ventricular tap is the most common method performed to diagnose central nervous system (CNS) infection in myelomeningocele patients. However, the ventricular tap can cause serious trauma to the baby and to the family. Here we discuss the technique of taking a cerebrospinal fluid (CSF) sample from the sac in myelomeningocele cases. Methods. The study comprised 24 myelomeningocele patients undergoing sac repair; 7 patients in the early period and 17 in the late period (after the first 24 hours). CSF samples were taken from the sac and via ventricular tap. In all patients' samples, cell count and cultures were compared. Results. In patients who underwent early meningomyelocele repair there was no significant difference between sac and ventricular CSF. There were also no positive cultures in samples taken from both areas. In comparison, in the group submitted to late repair, the number of cells in the sac and ventricle CSF samples was over 10 in 4 of the 17 patients. The cultures from CSF samples taken from both areas were positive for E. coli. In 13 of 17 patients who were admitted to our clinic for late repair, there was no significant difference between the number of cells in the sac and in ventricular samples. Cultures taken from these patients were negative. Conclusion. Puncture of the sac represents a quicker and more convenient way to obtain CSF in myelomeningocele cases. In addition, there was no increase in pain to a level that would cause stress for the baby. A CSF sample can be taken from the sac for diagnosis of CNS infection in myelomeningocele patients. This method, therefore, represents a safer and more comfortable option for both the patient and doctor.
Keywords: Cerebrospinal fluid; CNS infection; Myelomeningocele; Ventricular tap